Pelatihan Kosakata Bahasa Inggris Pariwisata (English For Tourism) Bagi Remaja Dan Praktisi Pariwisata Di Istana Maimun - A Arifuddin; Ratna Sari Dewi; Z Zuindra; M Mayasari (Jurnal TUNAS, 2021)
Maimun Palace is a deli royal heritage palace which was led by Sultan Al-Rasyid Perkasa Alamsyah in 1973. Maimun Palace is a tourist destination not only because of its old age but also its unique interior design that combines elements of deli cultural heritage.  Currently Maimun Palace has become a tourist destination for both local and foreign tourists.  As one of the most important aspects of tourism, youth tourism needs to be equipped with vocabulary skills in English.  This training aims to train and improve the English vocabulary skills of tourist youth, and to make the interaction of youth between foreign tourists and local communities so that the community and youths must be able to understand vocabulary so that they can carry out communication in English.  .  Therefore, the purpose of this activity is to increase the ability of English vocabulary for teenagers to support tourism activities, understand some vocabulary in the tourist environment to optimize the basic English skills possessed by teenagers and practitioners in communicating both orally and in writing.  The method used in this training is learning to increase the number of vocabulary in communicative language concepts.